ANALYSIS OF ETHICS OF GOVERNMENT APPARATUS BEHAVIOR IN PUBLIC SERVICE BASED ON LAW NUMBER 25 OF 2009 IN TAMALATE DISTRICT - Nur Azizah Anwar; Eka Fitra Ramadani; Mutmainnah, Inayatul (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to implement the work ethics of government employees in providing public services in Tamalate District based on Law Number 25 of 2009 concerning Public Services. This study uses a qualitative method with a case study approach in administrative services in Tamalate District. Data were collected through in-depth interviews with government employees and service users, direct observation of the service process, and analysis of relevant documents. The results of the study indicate that the work ethics of government employees in providing public services is still not optimal. Some employees exhibit unprofessional behavior, such as slow service delivery, lack of empathy towards the public, and low transparency in the service process. However, there are also employees who demonstrate positive behavior, such as providing clear and accurate information, and praying friendly and patient in serving the public. This study concludes that improving the work ethics of government employees is essential through public service ethics training programs, strict supervision, and regular evaluation and monitoring of employee performance. This effort is crucial to ensure public services meet the standards of professionalism, transparency, and accountability as mandated by Law Number 25 of 2009. The results of this study are expected to contribute to improving the quality of public services in Tamalate District and serve as a reference for similar research in the future.